Cultivation of human keratinocytes without feeder cells on polymer carriers containing ethoxyethyl methacrylate: in vitro study - Vacík, Jirí; Dvoránková, Barbora; Michálek, Jirí; Prádný, Martin; Krumbholcová, Eva; Fenclová, Tatána; Smetana, Karel (Journal of materials science. Materials in medicine, 2008)
The cell/tissue engineering therapy of extensive or chronic skin wounds is a highly topical task of the contemporary medicine. One of possible therapeutic approaches is grafting of in vitro cultured keratinocytes directly to the wound bed, where the cells colonize the wound, proliferate and improve the re-epithelization process. Because the successful cultivation of keratinocytes needs an application of feeder cells, the exclusion of these cells from the cultivation system is highly required. In this study we show a positive influence of 2-ethoxyethyl methacrylate as a component of cultivation support on growth of keratinocytes without feeder cells. Keratinocytes cultured on these surfaces are able to migrate to the model wound bed in vitro, where they form distinct colonies and have a normal differentiation potential.
Keywords: Biocompatible Materials; Culture Media; Cells, Cultured; kultivované buňky; buněčné kultury; Polymers; Methacrylates; keratinocyty; biokompatibilní materiály; Keratinocytes; Humans; polymery; methakryláty; Cell Culture Techniques; lidé; kultivační média